Sistema único de assistência social: o pacto de aprimoramento da gestão no município de Imperatriz – MA à luz do federalismo brasileiro - Tavares, Patrícia Aguiar (Universidade Federal do Tocantins, 2019)
This dissertation discusses the Single Social Assistance System and the municipal management improvement pact. The objective of the research was to implement the Single Social Assistance System (SUAS) for the four - year period 2014 - 2017, in the municipality of Imperatriz - MA in the light of Brazilian federalism. The study emphasized the conceptual, theoretical and higher aspects of the federalism and trajectory of social assistance in the Brazilian federation, which contributed to understand the model of political-administrative organization adopted and the reflexes in the policy of attention, as well as the mechanisms of cooperation and the federative pacts adopted. The methodology adopted is based on the analytical research modality of a qualitative nature, with data collection through bibliographic, documentary and interview research, search for information on search and execution strategies, and policy and implementation of the improvement pact Management of SUAS. For the data treatment, the content analysis method was used. Empirical research was carried out with managers of municipal social social policy, covering areas of Management, Basic Social Protection, Special Social Protection and Social Control. It has been lost that the federative model is adopted after the Federal Constitution of 1988, with decisions on the way they are decentralized and implemented as actions of the policy of social assistance locally. The results obtained demonstrate that they are effective as goals and targets by the municipality in the period between 2014 - 2017. The municipality does not have a planning aimed at compliance with the Pact of improvement of the Municipal Management of SUAS. The process of organization and articulation between the states, in order to implement the process of precariousness of a precarious action, the process of federal governance, between states, states and municipalities.